A Study on Bengal Partition: The Impact of Muslim Rule and British Occupation in Bengal (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Bengal in ancient literatures is mentioned as a distinct region ofSouth Asia, and throughout the first millennium A.D. it was governed by asuccession of Buddhist and Hindu rulers. Muslim armies arrived in the region inthe late twelfth and early thirteenth centuries, and gradually their conquestculminated in Mogul rule after 1576. During the 1500’s, British, Dutch, French,and Portuguese traders competed for control of  profitable trade between the East Indies and Europe. By the 1600’s,European trade settlements had cropped up in Bengal. The English government in1600 to develop trade with India and the Far East chartered the East IndiaCompany (a mercantile company of England). By the mid-1700’s, the company hadbecome the strongest trade power in Bengal. Later, England took overBengal  Administration  in 1757. At  first,  the Europeans  met  strong resistance  from Nawabs  who  were in  command  of the  territories.  They demanded taxes in return for tradeprivileges. But after the Mogul Empire weakened towards 1700’s, the Europeansincreased their influence. Ambitious Mogul Nawabs, nobles, and generalscompeted for power. The Europeans took sides in many of these conflicts,offering their support in return for monopoly trade privileges and otherrewards. East India succeeded in buying the Diwani (financial instrument) ofhuge Bengal state that comprised Bihar, Orissa and Assam from Emperor Shah Alamfor Rs.26 lacks, sealing off the Muslim hold on the state for ever.  Nawab Sirajudowla, (1756-1757), was the lastindependent Nawab of Bengal. He lost to the British Empire in the battle ofPlessey, 23 June 1757. British company forces were led by Robert Clive. TheMuslim rule established in Bengal by Turk soldier Ikhtiaruddin Muhammad-binBakhtiar 500 years ago came to a traumatic demise. The people of Bengal couldnot accept the British rule. ‘Fakir’ and  ‘Sanyashi’ revolutions during1760-1800, and  ‘Nil-Chashi’ (Indigofarmers) movement challenged the British reign from the very outset. Under theleadership of Haji Shariatullah and Titumir the Bengalis kept the Britishniggling and at tenterhooks from 1831-1839.  The Indian Soldiers, including Bengalis, revolted against the British in1857. Karl Marx termed the revolt as the first ever movement for Independenceby Indians. In May 1857 they revolted in Barackhpore, West Bengal, and on 18November in Chittagong. On 22 November the revolt spread to Dhaka. However withthe machination of Khawja Abdul Ghani the British overcame the challenge. Ghaniwas later rewarded with the 'Nawab' title. After  1857, several  secretaries  of state  for  India as  well  as Lieutenant  – Governors of  Bengal thought of  readjustment of boundaries of  the Province because it was too large andactually in 1874 the creation of Assam as a Chief Commissioner’s province towhich were attached the Bengali – speaking districts of Sylhet, Cachar andGoalpara was intended to reduce the size of Bengal to comparatively manageableproportion.